1990
DOI: 10.2307/4087626
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Ratio of Feathers Reveals Feeding Behavior of Cormorants

Abstract: A colony (ca. 2,000 birds) of the Great Cormorant (Phalacrocorax carbo) is present in Shinobazunoike Pond, Tokyo, Japan. The cormorants feed in rivers and in Tokyo Bay. The major direction of their daily flight in winter is to the rivers, and in summer to the Bay (Fukuda 1985). The relative importance of the two feeding sites in terms of dietary contribution is unknown. Dietary studies conventionally depend on stomach contents, cast pellets, and field observations. Although useful to reveal birds' choice of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 10 publications
8
96
0
1
Order By: Relevance
“…The mechanism responsible for the observed positive linear relationship between ␦ 13 C and ␦ 15 N values in feathers is also unknown. Similar patterns of intraspecific covariation of ␦ 13 C and ␦ 15 N values have been reported for humans (54), deer (55), elephants (61), bear (62,63), and cormorants (64). Some authors have suggested that the positive correlation may be a linked response to trophic enrichment of both 13 C and 15 N (reviewed in ref.…”
Section: Discussionsupporting
confidence: 52%
“…The mechanism responsible for the observed positive linear relationship between ␦ 13 C and ␦ 15 N values in feathers is also unknown. Similar patterns of intraspecific covariation of ␦ 13 C and ␦ 15 N values have been reported for humans (54), deer (55), elephants (61), bear (62,63), and cormorants (64). Some authors have suggested that the positive correlation may be a linked response to trophic enrichment of both 13 C and 15 N (reviewed in ref.…”
Section: Discussionsupporting
confidence: 52%
“…Mizutani et al (1992) extended this work to include other bird species and showed that ε feather-diet varied from 2.5 to 3.8‰, depending on species. Mizutani and Wada (1988), Mizutani et al (1990Mizutani et al ( , 1992 and Hobson and Clark (1992b) also observed significant differences in ε 13 C for regurgitant and feathers from free ranging and captive birds. Variability was attributed to a variety of factors including the relationship between the timing of feather growth and seasonality in the composition of potential prey and/or the lipid content of prey items (Bender et al 1981;Sullivan and Krueger 1981;Hobson and Clark 1992a).…”
Section: Stable Isotopes and Tissue-diet Enrichment Factorsmentioning
confidence: 97%
“…Mizutani et al (1990Mizutani et al ( , 1991 reported a ε feather-diet of 4‰ for stable carbon isotopes in free-ranging and captive cormorants and attributed the difference to the fractionation of 13 C as it is incorporated in the keratin of feathers. Mizutani et al (1992) extended this work to include other bird species and showed that ε feather-diet varied from 2.5 to 3.8‰, depending on species.…”
Section: Stable Isotopes and Tissue-diet Enrichment Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 6' " value can provide information about the source of carbon entering the food chain, for example distinguishing between marine and freshwater systems (Hobson 1987, Mizutani et al 1990, Hobson & Sealy 1991. Furthermore, the timescale over which dietary information is represented by a given isotope signature varies with tissue type and depends largely upon metabolic turnover (Tieszen et al 1983, Hobson & Sealy 1991, Hobson & Clark 1992a, 1993, Hobson 1993.…”
Section: Introductionmentioning
confidence: 99%